(untitled) (Journal of Scientific Research, 2009)
We present here cordial and 3-equitable labeling for the graphs obtained by joining apex vertices of two shells to a new vertex. We extend these results for k copies of shells. Keywords: Cordial labeling; 3-equitable labeling; Shell. © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v1i3.2227 J. Sci. Res. 1 (3), 438-449 (2009)